CTNI-27. SINGLE AGENT ACTIVITY OF ONC201 IN NON-MIDLINE H3 K27M-MUTANT DIFFUSE GLIOMAS. (12th November 2021) - Odia, Yazmin; Sumrall, Ashley; Cloughesy, Timothy; Nghiemphu, Phioanh; Hall, Matthew; Daghistani, Doured; Mehta, Minesh; Lassman, Andrew; Arrillaga-Romany, Isabel; Gardner, Sharon; Tarapore, Rohinton; Lu, Guangrong; et al.
Abstract: BACKGROUND: H3 K27M-mutant diffuse midline glioma is an invariably lethal form of brain cancer that disproportionately affects children and young adults and has no effective treatment following front-line radiation. The initial disease definition in the 2016 WHO Classification of Tumors of the Central Nervous System regarded the H3 K27M mutation as pathognomonic, though the definition was updated in 2018 restricting the diagnosis to histologically diffuse gliomas that involve midline CNS structures (cIMPACT-NOW update 2). ONC201 is an investigational anti- cancer small molecule, DRD2 antagonist and ClpP agonist that has induced durable tumor regressions by RANO-HGG criteria in a registration cohort of recurrent diffuse midline glioma, H3 K27M-mutant patients treated with single agent ONC201. METHODS: We present 7 patients with H3 K27M-mutant diffuse gliomas were enrolled in ONC201 clinical studies, excluded from the registration cohort due to involvement of non-midline CNS structures, all within the cerebral hemispheres (3 frontal, 1 temporal, 1 frontotemporal, 1 parietal, and 1 corona radiata). RESULTS: Two of the 7 patients underwent objective responses by RANO-HGG criteria as assessed by investigator, which was associated with clinical benefit that included increased mobility and level of alertness. CONCLUSIONS: These results demonstrate that H3 K27M-mutant diffuse gliomas occur outside of midline CNS structures, and suggest that ONC201 has single agent activity in H3 K27M-mutant gliomas irrespective of CNS location.